2019
DOI: 10.5005/jp-journals-10024-2521
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ Knowledge, Attitude and Practice of Root Canal Treatment Procedure: Survey-based Research

Abstract: Aim:The aim of this survey was to assess the dentists' knowledge, attitude and practice of endodontic treatment procedures and materials in Damascus city (capital of Syria), and the effect of endodontic specialty and years of experience on the survey findings.Materials and methods: Two hundred direct contacts (25 multiple-choice questions containing) questionnaires were distributed to randomly selected dentists practicing in Damascus city in 11 different areas, and a questionnaire contained questions regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
12
0
2
Order By: Relevance
“…A study from USA demonstrated a clear inclination to single visit endodontics especially in cases without apical periodontitis. (21) Due to lack of experience and clinical skills in performing single visit endodontic treatment, some dentists prefer to treat in multiple visits. (9) They may wait until the subsidence of pain and other symptoms before obturating the root canal/s.…”
Section: Discussionmentioning
confidence: 99%
“…A study from USA demonstrated a clear inclination to single visit endodontics especially in cases without apical periodontitis. (21) Due to lack of experience and clinical skills in performing single visit endodontic treatment, some dentists prefer to treat in multiple visits. (9) They may wait until the subsidence of pain and other symptoms before obturating the root canal/s.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this was due to the fact that patients were unaware of endodontics 2,20 . In previous studies, the most important criterion for patients was the skill and experience of the staff 6,8,21 , which we noticed, too. More than half of the participants reported their endodontics treatment done before.…”
Section: Discussionmentioning
confidence: 83%
“…Pain experience causes patients to hesitate the treatment and become more frightened of it 8 . The main reason for patients to avoid going to the dentist was the fear of pain 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations